The ICT convergence and impact on women-owned micro and small business enterprises: an analysis based on information poverty. (22nd January 2020) - Etim, Alice S.
Studies in the last two decades have helped to establish widespread mobile phone adoption in many populations including the region of Sub-Saharan Africa (SSA). Nigeria, the largest country in SSA by population (200 million, 2019) has had extensive growth in mobile telephone subscription. The literature, however, has limited coverage for smart technologies and internet adoption for business operations, specifically for women owned micro and small business enterprises. In addition, there are limited resources in the literature on convergence of the internet and smartphones for business operations. This study fills the void and reports a study on women entrepreneurs in the region of South Eastern Nigeria and their adoption/convergence of internet and mobile phones for business operations. Elfreda Chatman's information poverty theory was used as the theoretical framework to argue that the women entrepreneurs were challenged with information poverty; thereby addressing the question: Are they information poor?